(untitled) (Research, Society and Development, 2021)
Visceral Leishmaniasis, known as calazar in Brazil, is caused by the etiological agent Leishmania infantum chagasi transmission of the disease occurs through the bite of the female of a hematophagous invertebrate belonging to the family of phlebotomies, popularly known as straw mosquito, a disease that causes clinical symptoms that can affect both animals and humans. The present study aims to investigate the percentage of cases of disease infections in the municipality of Guaraí, Tocantins, in humans and animals (dogs), seeking to understand the factors that influence the prevalence of the disease in the municipality. This is documentary research, with a quantitative approach. The data were obtained from the analysis of documents contained in the municipal Health Department and the Zoonosis Control Center of the municipality between the years 2015 to 2020. Through the present study, it was noticed that the rate of affected by the disease in humans is much lower than in animals, because within the analyzed period, 15 tests confirmed with the disease were totaled in humans and 1,752 confirmed tests in animals. Public policies should be adopted to minimize the effects generated by the disease in both animals and humans, reducing the amount of litter, reducing errant dogs and adopting environmental education in the municipality.